Successful Settlement of Debts and Receivables Using Mediation Mechanisms - Chasanah, Kania Amru; Fuad Attamimi, Zeehan (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Humans as social beings are always bound in various social relationships that require rules to regulate interactions and avoid conflicts. In the legal context, agreements made between parties play an important role in the formation of legal relationships, and are regulated in the Civil Code (KUHPerdata). One of the methods of dispute resolution in the legal world is through mediation, which is regulated in Supreme Court Regulation (PERMA) No. 1 of 2016. Mediation is considered a more efficient and effective alternative to litigation, especially in the business world which often faces debt and receivable disputes. This study aims to examine the success of debt and receivables dispute resolution through mediation between PT SukaSari Mitra Mandiri as a creditor and UD Jayadi as a debtor. The research method used is normative juridical with an analytical descriptive approach, utilizing primary and secondary data obtained from through interviews and literature studies. The results of the study show that mediation can resolve debt and receivables disputes by producing a peaceful agreement that benefits both parties. This mediation process prioritizes the value of justice and efficiency, where the parties can resolve problems without going through the courts. An evaluation of compliance with a mediation agreement is also important to ensure that both parties meet their obligations as agreed, with potential legal action if either party does not comply with the agreement. This research provides insight into the importance of mediation as a dispute resolution mechanism in the world of business and civil law.